2008
DOI: 10.1130/b26055.1
|View full text |Cite
|
Sign up to set email alerts
|

Holocene debris flows on the Colorado Plateau: The influence of clay mineralogy and chemistry

Abstract: Holocene debris fl ows do not occur uniformly on the Colorado Plateau province of North America. Debris fl ows occur in specifi c areas of the plateau, resulting in general from the combination of steep topography, intense convective precipitation, abundant poorly sorted material not stabilized by vegetation, and the exposure of certain fi ne-grained bedrock units in cliffs or in colluvium beneath those cliffs. In Grand and Cataract Canyons, fi ne-grained bedrock that produces debris fl ows contains primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The proportion of rock blocks is large, while the total amount of less than 200 mm blocks is also relatively large, which is easy to initiate. Webb et al (2008) investigated the relationship between the clay mineralogy and major-cation chemistry of fine-grained bedrock units and the occurrence of debris flows on the entire Colorado Plateau, finding that the debris flow producers are uniformly low in montmorillonite (5%) and high in illite and kaolinite (71%); conversely, fine-grained bedrock that does not produce debris flows has lower illite and kaolinite (25%) and higher montmorillonite (51%) content. Analysis of the clay mineral composition of the deposit source in the meizoseismal area by X-ray diffraction experiments revealed that it is mainly composed of three clay minerals (Figure 7): illite, chlorite, and illitemontmorillonite mixed-layer, with an average content of 45.6%, 38.8%, and 15.6% respectively.…”
Section: Rainfall and Source Characteristicsmentioning
confidence: 99%
“…The proportion of rock blocks is large, while the total amount of less than 200 mm blocks is also relatively large, which is easy to initiate. Webb et al (2008) investigated the relationship between the clay mineralogy and major-cation chemistry of fine-grained bedrock units and the occurrence of debris flows on the entire Colorado Plateau, finding that the debris flow producers are uniformly low in montmorillonite (5%) and high in illite and kaolinite (71%); conversely, fine-grained bedrock that does not produce debris flows has lower illite and kaolinite (25%) and higher montmorillonite (51%) content. Analysis of the clay mineral composition of the deposit source in the meizoseismal area by X-ray diffraction experiments revealed that it is mainly composed of three clay minerals (Figure 7): illite, chlorite, and illitemontmorillonite mixed-layer, with an average content of 45.6%, 38.8%, and 15.6% respectively.…”
Section: Rainfall and Source Characteristicsmentioning
confidence: 99%
“…Further strengthening the distinction between the boundary and the interior of the Colorado Plateau is the distribution of cytotypes (Table 1) While distinct climate patterns, such as divergence in MAP (National Research Council, 2007;PRISM Climate Group, 2004) and MAT (PRISM Climate group, 2004), drive the differentiation of ecosystems on the Colorado Plateau, with drylands dominant in the interior and pinyon-juniper and montane forests dominant at and above the boundary (National Park Service, 2016), other biotic and abiotic factors may further shape the genetic variation observed in blue grama between these two regions. For example, the interior and the boundary regions of the Colorado Plateau also have markedly different topologies, soils, fire return intervals, and drought intensity patterns (Fule, Covington, & Moore, 1997;Miller & Tausch, 2001;Reynolds, Belnap, Reheis, Lamothe, & Luiszer, 2001;The National Drought Mitigation Center, 2017;Webb, Griffiths, & Rudd, 2007).…”
Section: Genetic and Environmental Correlationsmentioning
confidence: 99%
“…According to previous studies [1][2][3][4][5][6], we have known that there occur many Quaternary debris-flow deposits in the southeastern (SE) marginal area of the Tibetan Plateau (TP), especially in valleys of the upper reach of the Jinsha River and that they can provide rich information for geomorphic evolution, tectonic movement or climate change and others. In valleys of the upper reach of the Jinsha River, Zhang [7] identified one planation surface, two erosion surfaces and seven levels of alluvial terraces.…”
Section: Introductionmentioning
confidence: 99%